If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 3(a + 4) = 0 Reorder the terms: 2a + 3(4 + a) = 0 2a + (4 * 3 + a * 3) = 0 2a + (12 + 3a) = 0 Reorder the terms: 12 + 2a + 3a = 0 Combine like terms: 2a + 3a = 5a 12 + 5a = 0 Solving 12 + 5a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 5a = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 5a = 0 + -12 5a = 0 + -12 Combine like terms: 0 + -12 = -12 5a = -12 Divide each side by '5'. a = -2.4 Simplifying a = -2.4
| 8(x+2)-8=17-3x-9+11x | | 60t^4-4at^2+12t= | | (2x-3)(4x-2)= | | 0.33333333333x+10=55 | | x=2x^2+7x+9 | | -a/25=8 | | -4+9(x-2)=16x+3-7x | | .45x+.05(14-x)=.10(-25) | | -8-11=-5x+23 | | 0.80.2=x | | q^2+q-20=0 | | -(6xy-12)+3(5xy+8)= | | (6x+5)-1.3=-1.9 | | 0.33x+10=55 | | 14p^3q^3-21p^2q^2+35pq= | | 400-5x=322-3x | | 2(7)+6+5(7)=55 | | 8789-3434=876x | | -11-r=4(r-4) | | 1/4(3x+5)-1/3(x+7)=6 | | (m)=10 | | 33*.33n=.99n | | 25y^2+10y+1= | | 3x=54+3x | | 14x-28=-56 | | 6(z-4)+8z-3= | | 1/3(x-4)=5x-4(x-1)+22/3 | | 2(x-2)+3=2x+6 | | 2x+7+x=7 | | 22-3x=1 | | 0.5(10x+8)=3x-6 | | x^2(x+4)+2x(x+4)-15(x+4)= |